Evaluation of the vulnerability of Huanghe estuary coastal wetlands to marine oil spill stress - Zhang, Xiao; Zhang, Chunchang; Chen, Xiao; Su, Penghao (Frontiers in Marine Science, 2024)
The Huanghe Estuary, which is characterized by dynamic hydrological and ecological processes, is highly susceptible to marine oil spills due to dense maritime traffic and extensive industrial activities. This study evaluated the vulnerability of estuarine wetlands in the Huanghe Estuary to oil spill stress using the Pressure-Situation-Sensitivity-Recovery (PSSR) framework. By employing the Geographic Information System (GIS) and the Analytic Hierarchy Process (AHP), this study categorized the vulnerability index (0-1) into five classes: Very Low (0-0.098), Low (0.098-0.125), , and Very High (0.224-1). The results indicate that the ships indicator has the highest weight, followed by oil rigs. In contrast, the number of chemical splash-proof suits and tugboats have the lowest weights. Wetland vulnerability under oil spill stress exhibited significant spatial variation, with higher vulnerability observed in areas closer to the coastline, such as the eastern part of Kenli County, the northern part of Wudi County, and the northern part of Hekou District. This study underscores the need for targeted measures and enhanced monitoring to mitigate the risks of large oil spills and protect the ecological integrity of the Huanghe Estuary. The findings presented herein provide critical information that will help policymakers and environmental managers implement effective conservation strategies and risk mitigation efforts in this ecologically sensitive and economically important region.